Rpl22 loss impairs the development of B lymphocytes by activating a p53-dependent checkpoint - Fahl, Shawn P. (J Immunol, 2015)
While ribosomal proteins facilitate the ribosome’s core function of translation, emerging evidence suggests that some ribosomal proteins are also capable of performing tissue restricted functions either from within specialized ribosomes or from outside of the ribosome. In particular, we have previously demonstrated that germline ablation of the gene encoding ribosomal protein Rpl22 causes a selective and p53 dependent arrest of αβ T cell progenitors at the β-selection checkpoint. We have now identified a crucial role for Rpl22 during early B cell development. Germline ablation of Rpl22 results in a reduction in the absolute number of B-lineage progenitors in the bone marrow beginning at the pro-B cell stage. Although Rpl22-deficient proB cells are hyporesponsive to IL-7, a key cytokine required for early B cell development, the arrest of B cell development does not result from disrupted IL-7 signaling. Instead, p53 induction appears to be responsible for the developmental defects, as Rpl22-deficiency causes increased expression of p53 and activation of downstream p53 target genes and p53-deficiency rescues the defect in B cell development in Rpl22-deficient mice. Interestingly, the requirement for Rpl22 in the B cell lineage appears to be developmentally restricted, since Rpl22-deficient splenic B cells proliferate normally in response to antigen receptor and toll receptor stimuli and undergo normal class switch recombination. These results indicate that Rpl22 performs a critical, developmentally restricted role in supporting early B cell development by preventing p53-induction.